Muscle activation in healthy subjects during single step up [Aktivace svalů u zdravých osob při nákroku na schod] - Jaroslav Opavský; Elisa Isabel Yanac Paredes (Palacky University, 2010)
BACKGROUND: The single step up is an integral movement performance for functional mobility and activities of daily living. During this activity the body has to be able to keep its balance and maintain a stable upright posture for performing voluntary movement. For this purpose the central nervous system creates different motor programs specific to the task. A motor programme is believed to contain the pre-programmed sequence of muscle activity prior to the initiation of the task, and includes both the muscle activity for the task, as well as postural muscle activity. OBJECTIVE: The aim of this paper was to examine the sequence of muscular activation, and to determine the timing of the involvement of selected trunk and leg muscles whilst stepping up. The further aim was to find out the most common muscle patterns in this model of motor activity in healthy subjects. METHODS: The bilateral electromyographic (EMG) signal from the gluteus maximus, biceps femoris and erectores spinae muscles were recorded using surface electromyography. The visual record of the step up performance was registered simultaneously with surface electromyography. The tested group consisted of 16 healthy (5 men with an average age of 23.6, 11 women with an average age of 23.2). They were monitored during the motor task - the step up task, that is which was performed by the dominant leg. The subject stood facing the step (height of the step = 20 cm). Upon request he/she stepped up with the right leg at a spontaneous speed. The motor task was completed by bringing the left leg up onto the step. RESULTS: During this task, we registered the activation of the right erector spinae muscle, right biceps femoris muscle, left erector spinae muscle and left biceps femoris muscle before the beginning of the visually recognizable movement. The most frequently registered pattern of activation on the side that carried out the step was: right biceps femoris muscle → right erector spinae muscle → right gluteus maximus muscle. Greater differences in the sequence of the muscle involvement were found on the side of the supporting leg. CONCLUSIONS: In conclusion, the findings have indicated that there exists variability in patterns of muscle activation during the step up task. [VÝCHODISKA: Nákrok na schod je součástí běžných denních motorických aktivit. Při jeho provádění musí být tělo schopno udržovat rovnováhu a stabilní vzpřímenou posturu za současného průběhu volního pohybu. K tomuto účelu vytváří centrální nervová soustava různé motorické programy, specifické pro daný úkol a obsahující předem programované sekvence zapojování svalů k zajištění provedení vlastního pohybu a k udržení postury během vykonávaného pohybu. CÍLE: Cílem práce bylo určení časové posloupnosti zapojení vybraných svalů trupu a dolních končetin při nákroku na schod. Dalším cílem bylo zjištění nejběžnějšího vzoru zapojování svalů v této modelové pohybové aktivitě u zdravých osob. METODIKA: U této práce byla snímána bilaterálně elektromyografická aktivita m. gluteus maximus, m. biceps femoris a m. erector spinae (v jeho lumbální části). Spolu s elektromyografickým signálem snímaným povrchovými elektrodami byl zaznamenáván i vizuální záznam provedení nákroku na schod. Soubor tvořilo 16 zdravých mladých probandů, všichni praváci (5 mužů, průměrný věk 23,6 let a 11 žen, průměrný věk 23,2 let), u kterých byly anamnesticky vyloučeny úrazy dolních končetin a páteře. Na povel nakročili probandi spontánní rychlostí na schod (výška schodu = 20 cm) pravou dolní končetinou. Pohybový úkol končil došlápnutím levou dolní končetinou na schod. Elektromyografické záznamy jednotlivých svalů byly hodnoceny z hlediska časového nástupu aktivace svalů ve vztahu k začátku pohybu pravé dolní končetiny, který byl určen podle videozáznamu. Časy nástupu aktivace jednotlivých svalů byly mezi sebou porovnány k určení časové posloupnosti zapojení svalů a k určení nejběžnějšího vzoru svalového zapojení při tomto úkolu. VÝSLEDKY: Při úkolu nákroku na schod jsme zaregistrovali aktivaci pravého m. erector spinae, pravého m. biceps femoris, levého m. erector spinae a levého m. erector spinae již před začátkem pohybu pravé dolní končetiny. Dále jsme pozorovali jako nejčastější svalovou sekvenci na nákročné (pravé) straně: pravý m. biceps femoris → pravý m. erector spinae → pravý gluteus maximus. Větší rozdíly v sekvenci zapojování svalů jsme zachytili na stojné (levé) dolní končetině. ZÁVĚRY: Výsledky naší studie prokazují variabilitu vzorů zapojování svalů při studovaném úkolu nákroku na schod u zdravých jedinců.]